The Best Property Right as an Implied Request in the Claim Demand - Carlos Virgilio Vara Bejarano (2019)
The Supreme Court of the Republic of Peru, has established as a criterion in its agreements and appeals, that in claim demands, when the parties claim property rights, they should no longer be declared inadmissible under the argument that they must previously determine who has the best property right, but right there, must be resolved as a controversial point. Now, when the best property right is determined as a controversial point to resolve the claim, it has been substantiated as if it were a purport, the parties exercising the guarantees that due process contains, including the audi alteram partem and the right to the test, to assert its property right and / or to question the other, but as it was not requested, a ruling on the merits can not be issued, this in merit to the principle by which only the parties can incorporate the or the petitions, having to do so in a clear and concrete manner [1], not admitting the possibility of the implied request and the judge must rule only on the petition. Also the court itself, established as a criterion that once the ruling on the claim has been issued, having determined the best property claim rights as a controversial point, the parties can initiate another process for better property rights, because ultimately there is no res judicata material on this point. As set out above, there would be two processes, which could be undertaken separately or accumulated, since these two possibilities are subject to the will of the parties concerned, however, if the claim takes place first, and then another process is initiated for better property rights, and both could be resolved in a single process, (especially taking into account the close relationship that one has with the other, where the property right is the main budget), the only thing that would be generated is delay and unnecessary costs, both for the parties as for the state itself. Thus stated, it would be convenient, in application of the principle of economy and procedural speed, taking into account the purposes of the process, that both claims are necessarily accumulated and that the express will of the parties is not requiredfor it, it is necessary then to incorporate a normative formula in the Code of Civil Procedure, which in this way eases the principle, so that it allows the judge to incorporate the declaration of a better property right as an implied request, when he notes the factual grounds in which both parties have property rights, so as to process them as a counter-claim.